NICKNAMES WITH MEANING “HUMAN FEATURES”: PARADIGMATIC ASPECT (Proceedings of Southern Federal University. Philology, 2014)
This article is devoted to the study of virtual onims of young Caucasians. To reveal the identity of nicknames of Caucasians and to display their linguistic picture of the world Internet onims are considered in terms of their assignment to different thematic groups, given their lexical characteristics. The basis for this classification is a central component of commonality in the semantic structure of a nickname. The novelty of this work is presupposed by the fact that for the first time there is an attempt in linguistics to examine virtual onims of Caucasians in the paradigmatic aspect. The analysis revealed graphic antonyms, representing a unique linguistic phenomenon. Also, it has been discovered the cause of the appearance of the ethnic component in the nicknames of Caucasians. The analysis hyper-hyperonimic relations of thematic groups of nicknames revealed linguistic and extralinguistic communication in nickname of these thematic groups, and with the help of diagnostic structures by E.L. Gizburg and G.E. Kreydlin it has been presented the ways of modeling these connections in the system of the Russian language.Having distributed the group of nicknames by thematic groups and giving them a brief graphic, semantic and lexical features, we concluded that the nickname is one of the most diverse, extensive and interesting means of self-identity on the Internet. Choosing and inventing nicknames in virtual reality, young Caucasians tend to express themselves using emotionally marked words, and sometimes hide from surrounding certain concepts and phenomena using encrypted words and characters known only to them and their close circle of friends.Key words: Web personality, personal neologisms, nicknames, names, subject group, ethnic specificity, paradigmatic relations.